ПЕДАГОГІЧНІ УМОВИ ФОРМУВАННЯ ГОТОВНОСТІ СТУДЕНТІВ ПЕДАГОГІЧНИХ ВУЗІВ ДО ІНСТРУМЕНТАЛЬНО-ВИКОНАВСЬКОЇ ДІЯЛЬНОСТІ - Кремешна, Тетяна; Обманець, Людмила (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті розглядається сутність та зміст поняття «готовність студентів до інструментально-виконавської діяльності» та педагогічні умови готовності майбутніх виконавців-інструменталістів до досліджуваної проблеми. Серед педагогічних умов автори виділяють: спецкурс «Формування готовності студентів до інструментально-виконавської діяльності» та стимулювання творчої самостійності майбутніх піаністів у навчальному середовищі вищого педагогічного закладу. Важливе місце відводиться аналізу категорії «готовність» та стану окресленої проблеми у музично-педагогічних дослідженнях вітчизняних та зарубіжних науковців. В статье рассматривается сущность и содержание понятия «готовность студентов к инструментально-исполнительской деятельности» и педагогические условия готовности будущих исполнителей инструменталистов к исследуемой проблеме. Среди педагогических условий авторы выделяют: спецкурс «Формирование готовности студентов к инструментально-исполнительской деятельности» и стимулирования творческой самостоятельности будущих пианистов в учебной среде высшего педагогического заведения. Важное место отводится анализу категории «готовность» и состоянию обозначенной проблемы в музыкально-педагогических исследованиях отечественных и зарубежных ученых. In the article the essence and meaning of «readiness of students to instrumental performance of» and pedagogical conditions of future singers, instrumentalists to study the problem. Among the authors identify pedagogical conditions: the special course «Formation of readiness of students to instrumental performance of» creative independence and stimulate future pianists in the educational environment of higher educational institutions. The important place given to the analysis category «readiness» status and problems outlined in the musical and pedagogical studies of domestic and foreign scientists. The author argues that the willingness of students to instrumentalists performing activity promotes professional excellence, enables young musician, teacher professional duties effectively, has a significant impact on the theory and practice of learning to play an instrument, as the game before the audience is in continuous mode activities and pedagogical conditions of future singers to instrumentalists such activities entrusted to develop creativity of students forming their creative position and ability to express themselves.